Toxic a tour of the Ecuadorian Amazon - Fiske, Anna 1964- (University of Toronto Press, 2024)
"Over the past decade, people have learned about oil contamination in the Ecuadorian Amazon through "Toxic Tours" in which a guide brings participants--students, lawyers, environmental activists, journalists, or foreign tourists--to visit contaminated sites. These toxic tours combine personal experience and local knowledge to convince visitors of the immediacy of environmental issues. Drawing on extensive research and fieldwork, Toxic takes the reader on a visual toxic tour through the Amazon. Following the story of three fictional participants, this graphic novel paints a visceral picture of the waste pits, gas flares, and precarious lives of people in this region. The book challenges the reader to consider what it means to live in a place and historical moment where those most burdened by industrial toxicants are continually required to prove that harm has occurred. Toxic is a vivid reflection on the role of pollutants in our everyday lives, ultimately asking readers to reflect on how we are each implicated in the production, consumption, and exposure of pollution both in the Amazon and at home."--
Keywords: ChevronTexaco Corporation; Umweltverschmutzung; Umwelttoxizität; Anwohner; Gesundheitsschaden; Erdölindustrie; Recht; Indigenes Volk; Ecuador; Petroleum industry and trade / Environmental aspects / Ecuador / Comic books, strips, etc; Petroleum industry and trade / Social aspects / Ecuador / Comic books, strips, etc; Pollutants / Ecuador / Comic books, strips, etc; Ecuador / Environmental conditions / Comic books, strips, etc; Ecuador / Tours / Comic books, strips, etc; Pétrole / Industrie et commerce / Aspect social / Équateur / Bandes dessinées; Polluants / Équateur / Bandes dessinées; Ecology; Petroleum industry and trade / Environmental aspects; Petroleum industry and trade / Social aspects; Pollutants; Electronic books; Comics (Graphic works); Bandes dessinées; Comic